Commonwealth Edison : the use of social media in disaster response - Diermeier, Daniel (SAGE knowledge. Cases., 2016)
After a massive storm hit the northern Illinois service area of electric utility Commonwealth Edison on July 11, 2011, more than 900,000 customers were left without power during a hot, humid summer. ComEd crews and reinforcements from more than a dozen other states worked for days afterward to restore service. Meanwhile, the company's months-old social media strategy faced its first major test. This case examines the company's efforts to engage with their customers through social media.